A unique race of the wheat stem rust pathogen with virulence on Sr31 identified in Spain and reaction of wheat and durum cultivars to this race. (14th February 2022) - Olivera, Pablo D.; Villegas, Dolors; Cantero‐Martínez, Carlos; Szabo, Les J.; Rouse, Matthew N.; Luster, Douglas G.; Bartaula, Radhika; Lopes, Marta S.; Jin, Yue
Abstract: Wheat stem rust, caused by Puccinia graminis f. sp. tritici, is a re‐emerging disease, posing a threat to wheat production. In Spain, stem rust has been rarely detected since the 1970s, but infection was observed in wheat fields in 2018. We analysed six stem rust samples collected in Rota, Cádiz province and one from Monteagudo del Castillo, Teruel province. All the samples from Rota were typed as race TKTTF, whereas the sample from Monteagudo del Castillo, collected in a wheat field adjacent to barberry bushes, was typed as race TKHBK. This race has a unique and significant virulence combination that includes virulence to Sr31, Sr33, Sr53 and Sr59, and is avirulent to Rusty, a durum line developed for universal susceptibility to the wheat stem rust pathogen. TKHBK is the first race outside the Ug99 race group with virulence to Sr31 and the first known race with virulence to Sr59 . Genotyping studies indicate that race TKHBK does not belong to the Ug99 or TKTTF race groups and constitutes a previously unknown lineage. Two hundred bread and durum wheat cultivars and breeding lines from Spain were evaluated against TKHBK, TKTTF, and six additional races. Resistance was observed to all the races evaluated. Molecular markers confirmed the presence of Sr7a, Sr24, Sr31, Sr38 and Sr57 in bread wheat, and Sr13 in durum wheat. The re‐emergence of wheat stem rust in Spain and the occurrence of unique virulences underscore the need to continue surveying and monitoring this disease. Abstract : Race TKHBK, a new strain of the wheat stem rust pathogen outside the Ug99 race group that attacks resistance genes Sr31 and Sr59, but with limited virulence to bread and durum wheat varieties, was found in Spain near barberry.